Upaya Pencegahan Kejadian Kanker Payudara Dengan Edukasi Pemeriksaan Payudara Sendiri (Sadari) pada Wanita di Kabupaten Kapuas - Ruslinawati Ruslinawati; Esty Yunitasari; Yenny Okvitasari; Kristina Yuniarti; Rr.Sri Nuriaty; M Rifqi; Sumiati Sumiati (Lembaga Pengembangan Kinerja Dosen, 2023)
The Ministry of Health of the Republic of Indonesia stated that the prevalence of cancer in 2003 was only 221 cases, in 2008 it had tripled to 657 cases and there were 1,722 total cases in 2010-2011. As many as 60-70% of breast cancer patients come with advanced stages (stage III or IV), so almost half of the incidence of breast cancer ends in death. Breast self-examination (BSE) is very important as a first step to find out whether you have breast cancer or not. The existence of information about BSE and breast cancer is a motivation for women to increase knowledge about the breast area. This is the main basis for increasing knowledge about breast examination Purpose This activity increases understanding of how to check BSE with leafliat media. The Activity Method provides health education and distributes leaflets. Activity Results: how to know the incidence of cancer is to know early the abnormalities of the female body itself, especially the breast. Conclusion: Health education with leafeat can increase knowledge and understanding of early detection of abnormalities in the woman's own body parts.